Assessment of the Ecological Quality Status of Sediment in the Organic Shrimp Farming Ponds Using Azti‟s Marine Biotic index Based on Marobenthic Communities - Thai, Tran Thanh; Quang, Ngo Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2, 2018)
Macrobenthic communities (MC) in the Tam Giang„s organic shrimp farming ponds (TGOSFP) (located in Tam Giang commune, Nam Can district, Ca Mau province) were explored during three seasons in 2015 (March - dry, July - transitional and November - rain season). The results indicated that the MC have characterized by high density and quite diverse. Further more, the present study is a first attempt to use of AZTI‟s Marine Biotic Index (AMBI) based on MC for determining the ecological quality status of sediment (EcoQ) in the TGOSFP. The following results were also recorded with an undisturbed and slightly disturbed EcoQ in the TGOSFP and the general EcoQ would likely be improved between three seasons. The success of AMBI for detecting EcoQ in Vietnam is specific to this study, but AMBI was likely to improved, in particular tropical regions. Keywords AMBI, Ca Mau province, ecological quality status of sediment, macrobenthic communities, organic shrimp farming ponds References [1]. H. Teixeira, S. B. Weisberg, A. Borja, J . A. Ranasinghe,, D. B. Cadien, R. G. Velarde, ... & J. K. Ritter, Calibration and validation of the AZTI's Marine Biotic Index (AMBI) for Southern California marine bays, Ecological Indicators 12 (2005) 84. [2]. S. Bustos - Baez, C. Frid, Using indicator species to assess the state of macrobenthic communities, Advances in Polychaete Research, Springer, 2003. [3]. C. J. Dauvin, T. Ruellet, N. Desroy, L. A. Janson, The ecological quality status of the Bay of Seine and the Seine estuary: use of biotic indices, Marine Pollution Bulletin 55 (2007) 241. [4]. D. P. Z Amitage, D. Moss, F. J. Wright, T. M. Furse, The performance of a new biological water quality score system based on macroinvertebrates over a wide range of unpolluted running - water sites, Water research 17 (1983) 333. [5]. J. Word, The infaunal trophic index, a functional approach to benthic community analyses, PhD thesis, University of Washington, 1990. [6]. B.S. Weisberg, A. J. Ranasinghe, M. D. Dauer, C. L. Schaffner, J. R. Diaz, B. J. Frithsen, An estuarine benthic index of biotic integrity (B-IBI) for Chesapeake Bay, Estuaries and Coasts 20 (1997) 149. [7]. J. Grall, M. Glémarec, Using biotic indices to estimate macrobenthic community perturbations in the Bay of Brest. Estuarine, Coastal and Shelf Science 44 (1997) 43.. [8]. A. Borja, J. Franco, V. Pérez, A marine biotic index to establish the ecological quality of soft-bottom benthos within European estuarine and coastal environments, Marine Pollution Bulletin 40 (2000) 1100. [9]. N. Simboura, A. Zenetos, Benthic indicators to use in ecological quality classification of Mediterranean soft bottom marine ecosystems, including a new biotic index, Mediterranean Marine Science 3 (2002) 77. [10]. R. Rosenberg, M. Blomqvist, C. H. Nilsson, H. Cederwall, A. Dimming, Marine quality assessment by use of benthic species-abundance distributions: a proposed new protocol within the European Union Water Framework Directive, Marine Pollution Bulletin 49 (2004) 728. [11]. F. Salas, C. Marcos, A. Pérez - Ruzafa, C. J. Marques, Application of the exergy index as ecological indicator of organically enrichment areas in the Mar Menor lagoon (south-eastern Spain), Energy 30 (2005) 2505. [12]. I. Muxika, A. Borja, J. Bald, Using historical data, expert judgement and multivariate analysis in assessing reference conditions and benthic ecological status, according to the European Water Framework Directive, Marine Pollution Bulletin 55 (2007) 16. [13]. N. C. Thuan, N. H. Chiem, D. T. Duong, Water quality assessment base on BMWPViet Nam at Cai May canal, Phu Tan district, An Giang province, Can Tho University Journal of Science 15 (2010) 125.. [14]. C. T. Truong, A. T. T. Ngo, Application of macroinvertebrates for assessment of water quality in 4 main canal systems in Ho Chi Minh city, Science & Technology Development 10 (2007) 25. [15]. N. V. Khanh, P. T. H. Ha, L. T. Son,. Using bioindicator macro invertebrates assessment of the water quality in five pools in Da Nang city, Hue University Journal of Science 63 (2010) 91. [16]. A. Borja, G. J. Rodríguez, K. Black, A. Bodoy, C. Emblow, F. T. Fernandes, ... N. Papageorgiou, Assessing the suitability of a range of benthic indices in the evaluation of environmental impact of fin and shellfish aquaculture located in sites across Europe, Aquaculture 293 (2009) 231. [17]. A. Afli, R. Ayari, S. Zaabi, Ecological quality of some Tunisian coast and lagoon locations, by using benthic community parameters and biotic indices, Estuarine, Coastal and Shelf Science 80 (2008) 269. [18]. L. Bigot, A. Grémare, M. J. Amouroux, P. Frouin, O. Maire, C. J. Gaertner, Assessment of the ecological quality status of soft-bottoms in Reunion Island (tropical Southwest Indian Ocean) using AZTI marine biotic indices, Marine Pollution Bulletin 56 (2008) 704. [19]. A. Bakalem, T. Ruellet, C. J. Dauvin, Benthic indices and ecological quality of shallow Algeria fine sand community, Ecological Indicators 9 (2009) 395. [20]. A. Borja, G. B. Tunberg, Assessing benthic health in stressed subtropical estuaries, eastern Florida, USA using AMBI and M - AMBI, Ecological Indicators 11 (2011) 295. [21]. Ministry of Agriculture and Rural Development (MARD), https://tongcucthuysan.gov.vn/en-us/aquaculture/doc-tin/006222/2016-10-28/ca-mau-set-outs-to-become-viet-nams-largest-shrimp-hub, Access 1 May. 2016. [22]. L. Lebel, H. N. Tri, A. Saengnoree, S. Pasong, U. Buatama, K. L. Thoa, Industrial transformation and shrimp aquaculture in Thailand and Vietnam: pathways to ecological, social, and economic sustainability?. AMBIO, A Journal of the Human Environment 31 (2002) 311. [23]. P. N. H, T. H. San, Mangroves of Vietnam (Vol. 7), IUCN 1993. [24]. Thai agricutural standard (TAS), Organic marine shrimp farming, Royal Gazette Vol. 124 Section 78E 2007. [25]. N. Tho, N. V. Ut, R. Merckx, Physico ‐ chemical characteristics of the improved extensive shrimp farming system in the Mekong Delta of Vietnam, Aquaculture Research 42 (2011) 1600. [26]. D. Johnston, M. Lourey, D. V. Tien, T. T. Luu, T. T. Xuan, Water quality and plankton densities in mixed shrimp‐mangrove forestry farming systems in Vietnam, Aquaculture Research 33 (2002) 785. [27]. T. T. Thai, N. T. M. Yen, N. Tho, N. X. Quang, Meiofauna in the mangrove – shrimp farms ponds, Ca Mau province, Journal of Science and Technology 55 (2017) 271. [28]. N. V. Thanh, N. N. Chau, The zoobenthos of Can Gio mangrove ecosystem. Publishing House for Science and Technology Hanoi Vietnam 2005. [29]. T. R. Abbott, S. Dance, T. Abbott, Compendium of seashells, Odyssey 1983. [30]. J. P. Hayward, S. J. Ryland, Handbook of the marine fauna of North - West Europe, Oxford University Press 1995. [31]. K. Fauchald, The polychaete worms; definitions and keys to the orders, families and genera, Natural History Museum of Los Angeles County 1977. [32]. J. F. Springsteen, M. F. Leobrera, B. C. Leobrera, Shells of the Philippines (Vol. 100), Carfel Seashell Museum, Manila 1986. [33]. G. A. Gao, Z. Q. Chen, N. J. Zeng, B. Y. Liao, Y. J. Yang, Macrofauna community in the mangrove area of Ximen Island, Zhejiang, Journal of Marine Sciences 23 (2005) 33. [34]. A. Saravanakumar, S. J. Serebiah, A. G. Thivakaran, M. Rajkumar, Benthic macrofaunal assemblage in the arid zone mangroves of gulf of Kachchh-Gujarat, Journal of Ocean University of China 6 (2007) 303. [35]. H. A. Parulekar, A. B. Waugh, Quantitative studies on the benthic macrofauna of northeastern Arabian sea shelf, Indian Journal Marine Science 4 (1975) 174. [36]. A. S. Netto, F. Gallucci, Meiofauna and macrofauna communities in a mangrove from the Island of Santa Catarina, South Brazil, Hydrobiologia 505 (2003) 159. [37]. J. Schrijvers, D. V. Gansbeke, M. Vincx, Macrobenthic infauna of mangroves and surrounding beaches at Gazi Bay, Kenya, Hydrobiologia 306 (1995) 53. [38]. T. Ysebaert, P. Meire, D. Maes, J. Buijs, The benthic macrofauna along the estuarine gradient of the Schelde estuary, Aquatic Ecology 27 (1993) 327. [39]. B. Thilagavathi, D. Varadharajan, A. Babu, J. Manoharan, S. Vijayalakshmi, T. Balasubramanian, Distribution and diversity of macrobenthos in different mangrove ecosystems of Tamil Nadu coast, India, Journal of Aquaculture Research & Development 4 (2013) 1. [40]. S. P. Kumar, B. A. Khan, The distribution and diversity of benthic macroinvertebrate fauna in Pondicherry mangroves, India, Aquatic biosystems 9 (2013) 15. [41]. J. Y. Tang,X. S. Yu, Y. Y. Wu, A comparison of macrofauna communities in different mangrove assemblages, Zoological Research 28 (2007) 255. [42]. S. Dittmann, Abundance and distribution of small infauna in mangroves of Missionary Bay, North Queensland, Australia, Revista de biología tropical 49 (2007) 535. [43]. L. C. Marte, The Food and Feeding Habit of Penaeus Monodon Fabricius Collected From Makato River, Aklan, Philippines (Decapoda Natantia) , Crustaceana 38 (1980). 225 [44]. I. Muxika, A. Borja, J. Franco, The use of a biotic index (AMBI) to identify spatial and temporal impact gradients on benthic communities in an estuarine area, ICES CM 2003. [45]. A. Borja, I. Muxika, J. Franco, The application of a Marine Biotic Index to different impact sources affecting soft-bottom benthic communities along European coasts, Marine Pollution Bulletin 46 (2003) 835. [46]. C. H. I. A. R. A. Casselli, M. A. S. S. I. M. O. Ponti, M. A. R. C. O. Abbiati, Valutazione della qualità ambientale della laguna costiera Pialassa Baiona attraverso lo studio dei suoi popolamenti bentonici. In XIII Congresso Societá Italiana de Ecología Como Villa Olmo 2003. [47]. V. Solis - Weiss, F. Aleffi, N. Bettoso, P. Rossin, G. Orel, S. Fonda - Umani, Effects of industrial and urban pollution on the benthic macrofauna in the Bay of Muggia (industrial port of Trieste, Italy), Science of the total environment 328 (2004) 247. [48]. M. P. A. Valença, J. P. Santos, Macrobenthic community for assessment of estuarine health in tropical areas (Northeast, Brazil): review of macrofauna classification in ecological groups and application of AZTI Marine Biotic Index, Marine pollution bulletin 64 (2012) 1809. [49]. P. Muniz, N. Venturini, M. A. Pires - Vanin,R. L. Tommasi, A. Borja, Testing the applicability of a Marine Biotic Index (AMBI) to assessing the ecological quality of soft-bottom benthic communities, in the South America Atlantic region, Marine Pollution Bulletin 50 (2005) 624.